Growth of black molly Poecilia sphenops (Poecilidae: Pisces) Reared in closed recirculating water system - Al-Faiz, Nawras A. A.; Khamees, Najim R.; Jasim, Basim M. (Iraqi Journal of Aquaculture, 2022)
The experiment was conducted study the effect of temperature and food composition on growth, food conversion efficiency, food conversion rate and quantity of food intake by larvae of black molly Poecilia sphenops in closed recirculating water system Three types of food were employed. The first (I) was live food, brine shrimp Artemia, the second (II) was experimental artificial diet and the third (III) was commercial diet. The three diets were served under two temperature: (28±1°C and 22±1°C). Results showed that under temperature 28±1°C, the total weight increment and relative growth rate were 2.98-5.87 g and 1865.62- 3671.87 respectively. In the temperature 22±1°C these values were significantly lower (p<0.05). The I and II higher values than treatments III with significant difference (p<0.05) in both thermal degrees. In the temperature (22±1°C) the food conversion rate and efficiency rate attained 2.052 and 48.746 respectively in treatment II which were higher than that of treatment III (2.686 and 37.220 respectively), the two items were greater in temperature 28±1°C, and at treatment II (1.662 and 60.177 respectively) in comparison with the treatment III (2.220 and 45.064 respectively), the treatment II higher values than III with significant difference(p<0.05) in both degrees. The food intake larger in the 28±1°C than degree 22±1°C with significant difference for both treatments II and III, food intake in treatment II was larger significantly (p<0.05) than III at degree 22±1°C and non significantly (p>0.05) at degree 28±1°C.